A multi-model assessment of the impact of currents, waves and wind in modelling surface drifters and oil spill. (November 2016) - De Dominicis, M.; Bruciaferri, D.; Gerin, R.; Pinardi, N.; Poulain, P.M.; Garreau, P.; Zodiatis, G.; Perivoliotis, L.; Fazioli, L.; Sorgente, R.; Manganiello, C.
Abstract: Validation of oil spill forecasting systems suffers from a lack of data due to the scarcity of oil slick in situ and satellite observations. Drifters (surface drifting buoys) are often considered as proxy for oil spill to overcome this problem. However, they can have different designs and consequently behave in a different way at sea, making it not straightforward to use them for oil spill model validation purposes and to account for surface currents, waves and wind when modelling them. Stemming from the need to validate the MEDESS4MS (Mediterranean Decision Support System for Marine Safety) multi-model oil spill prediction system, which allows access to several ocean, wave and meteorological operational model forecasts, an exercise at sea was carried out to collect a consistent dataset of oil slick satellite observations, in situ data and trajectories of different type of drifters. The exercise, called MEDESS4MS Serious Game 1 (SG1), took place in the Elba Island region (Western Mediterranean Sea) during May 2014. Satellite images covering the MEDESS4MS SG1 exercise area were acquired every day and, in the case an oil spill was observed from satellite, vessels of the Italian Coast Guard (ITCG) were sent in situ to confirm the presence of the pollution. During the exercise one oil slick was found in situ and drifters, with different water-following characteristics, were effectively deployed into the oil slick and then monitored in the following days. Although it was not possible to compare the oil slick and drifter trajectories due to a lack of satellite observations of the same oil slick in the following days, the oil slick observations in situ and drifters trajectories were used to evaluate the quality of MEDESS4MS multi-model currents, waves and winds by using the MEDSLIK-II oil spill model. The response of the drifters to surface ocean currents, different Stokes drift parameterizations and wind drag has been examined. We found that the surface ocean currents mainly drive the transport of completely submerged drifters. The accuracy of the simulations increases with higher resolution currents and with addition of the Stokes drift, which is better estimated when provided by wave models. The wind drag improves the modelling of drifter trajectories only in the case of partially emerged drifters, otherwise it leads to an incorrect reproduction of the drifters׳ direction, which is particularly evident in high speed wind conditions.